Bioethanol production from rice straw using Saccharomyces cerevisiae, Pichia stipitis ATCC 58785 and their Fusants - Shalsh, Fawzia Jassim (2019)
Bioethanol has been gaining attention as a clean and renewable fuel because of its immense environmental benefits. Worldwide bioethanol demand has been continuously increasing due to the rapid growth in population and industrialization. To overcome this growing need, this study aims to increase bioethanol production by using effective microorganisms to utilize all sugars in biomass through advanced fermentation techniques. Saccharomyces cerevisiae is a widely-used microorganism for production of bioethanol. But unfortunately, it is unable to ferment xylose, which is the second most abundant source of sugar in plant tissues. Therefore, the need to develop an effective microorganism that could maximize the utilization of glucose and xylose to produce bioethanol. A protoplast fusion between S. cerevisiae and xylose-fermenting yeast Pichia stipitis ATCC 58785 was conducted to produce the fusant which could improve bioethanol production. The protoplast isolation was achieved using zymolyase 20T. The total protoplast fusion was at a rate of 52.21%. Among 60 fusants, five fusants were chosen according to their ability to utilize glucose and xylose and ethanol tolerance. The co-fermentation and co-culture fermentation approaches were conducted by using S. cerevisiae, P. stipitis ATCC 58785 and the fusants in a stirred tank bioreactor for bioethanol production. Co-fermentation was achieved by P.stipitis ATCC 58785 in the medium containing the glucose and xylose mixture. P.stipitis ATCC 58785 fermented both sugars and produced 28.30 g/L bioethanol. The co-culture fermentation of S. cerevisiae and P. stipitis ATCC 58785 produced 30.12 g/L bioethanol. Among the five selected fusants, the fusant F24 was able to attain maximum bioethanol production from the glucose-xylose mixture. The fusant F24 produced 30.24 g/L bioethanol. Rice straw is a promising lignocellulosic biomass for bioethanol production. One of the significant challenges in developing technology for bioethanol production from rice straw is the selection of an appropriate pretreatment technique that could make the whole process economically viable. The outcomes of pretreatment using alkaline and dilute acid hydrolysis were evaluated using Response Surface Methodology (RSM) to establish the optimum hydrolysis processing criteria for rice straw. The highest rate of sugar produced after acid hydrolysis was at a rate of 24.55 g/L followed by saccharification at a rate of 87.8% and 14.8% for xylose and glucose, respectively. Sequential alkaline–acid hydrolysis was found to be capable of reducing the consumption of pretreatment agents in addition to its ability to disrupt the surface of the rice straw as confirmed by Scanning Electron Microscope (SEM) analysis. Bioethanol production from fermentation of the hydrolyzed rice straw was investigated. The fusant F24 showed promising results of 5.41g/L of produced bioethanol compared to 1.12 g/L, 3.14 g/L, 5.01 g/L for S. cerevisiae, P. stipitis ATCC 58785 and co-culture fermentation respectively. The fermentation using fusant gives the advantage to the production of bioethanol by reducing the duration of fermentation.